The Influence of Service Quality on the Purchasing Power of Students at Bhakti Asih Purwakarta Polytechnic (Case Research of Resto CFC Yogya Purwakarta) - Sari, Puspa Yudhyastuti Indah (Green Publisher Indonesia, 2025)
The rapid development of the fast-food industry in Purwakarta has led to intense competition among restaurants, including CFC Toserba Yogya. Service quality is one of the key factors in maintaining and enhancing customer purchasing power, particularly among students. Good service creates satisfaction and loyalty, which encourage repeat purchases and recommendations from customers. This research aims to analyze the influence of service quality, food quality, and price/value on the behavioral intention of students toward CFC Yogya Purwakarta, specifically focusing on factors that drive student purchasing decisions in the competitive fast-food market. This research used a quantitative approach with a survey method through the distribution of questionnaires to 50 student respondents who had visited CFC Toserba Yogya Purwakarta. Data analysis techniques included SPSS 23 with validity, reliability, descriptive analysis, classical assumption tests, and regression tests. The statistical analysis reveals significant findings: service quality demonstrates a positive and significant influence on behavioral intention (p = 0.043 < 0.05); food quality shows a strong positive correlation with purchase intention (r = 0.785, p < 0.001); and price/value perception significantly affects behavioral intention (p < 0.001). The demographic analysis indicates that 90% of respondents are female students aged 18–20 years with monthly expenditures below Rp 500,000, who prioritize cleanliness, service speed, and the value-for-money ratio in their dining decisions. The research concludes that integrated improvement in service quality, food quality, and price perception creates synergistic effects on student behavioral intentions, with service quality being the primary driver of repeat purchase behavior among polytechnic students.